Vitamin intake is associated with improved visuospatial and verbal semantic memory in middle-aged individuals - Flitton, Miles; MacDonald, Ian A.; Knight, Helen M. (Taylor and Francis Group, 2019)
Objectives: Factors maintaining cognitive health are still largely unknown. In particular, the cognitive benefits associated with vitamin intake and vitamin supplementation are disputed. We investigated self-reported vitamin intake and serum vitamin levels with performance in cognitive factors sensitive to dementia progression in two large middle-aged general population cohorts.